Descriptive of School Environmental Conditions on Student Learning Achievement - Navia, Nur’ Ayunin; Ramadhan, Galang; Alvares, Mochammad Rifqi (Procedia of Social Sciences and Humanities, 2024)
This study investigates the important role of school environment conditions on student learning achievement at Muhammadiyah Junior High School 1 Sidoarjo, which emphasizes moral and ethical values. Using a qualitative approach, data were collected through observations and interviews over approximately five days. The results revealed positive habits such as 3s (smile, greeting, salutation), adequate facilities, and effective learning processes. Play an important role in improving student learning achievement. Teachers at the school contribute greatly to character development and achievement by motivating students. The impact of these activities can improve strong morale, good social skills, high motivation, and quality learning ability.